Increasing human monoclonal antibody cloning efficiency with a whole-cell modified immunoglobulin-capture assay (mICA) - Siris, Sara; Gladstone, Camilla A.; Guo, Yanping; Patel, Radhika; Pinder, Christopher L.; Shattock, Robin J.; McKay, Paul F.; Langford, Paul R.; Bidmos, Fadil A. (Frontiers in Immunology, 2023)
Expression cloning of fully human monoclonal antibodies (hmAbs) is seeing powerful utility in the field of vaccinology, especially for elucidating vaccine-induced B-cell responses and novel vaccine candidate antigen discovery. Precision of the hmAb cloning process relies on efficient isolation of hmAb-producing plasmablasts of interest. Previously, a novel immunoglobulin-capture assay (ICA) was developed, using single protein vaccine antigens, to enhance the pathogen-specific hmAb cloning output. Here, we report a novel modification of this single-antigen ICA using formalin-treated, fluorescently stained whole cell suspensions of the human bacterial invasive pathogens, Streptococcus pneumoniae and Neisseria meningitidis. Sequestration of IgG secreted by individual vaccine antigen-specific plasmablasts was achieved by the formation of an anti-CD45-streptavidin and biotin anti-IgG scaffold. Suspensions containing heterologous pneumococcal and meningococcal strains were then used to enrich for polysaccharide- and protein antigen-specific plasmablasts, respectively, during single cell sorting. Following application of the modified whole-cell ICA (mICA), 61% (19/31) of anti-pneumococcal polysaccharide hmAbs were cloned compared to 14% (8/59) obtained using standard (non-mICA) methods – representing a 4.4-fold increase in hmAb cloning precision. A more modest 1.7-fold difference was obtained for anti-meningococcal vaccine hmAb cloning; 88% of hmAbs cloned via mICA versus 53% cloned via the standard method were specific for a meningococcal surface protein. VDJ sequencing revealed that cloned hmAbs reflected an anamnestic response to both pneumococcal and meningococcal vaccines; diversification within hmAb clones occurred by positive selection for replacement mutations. Thus, we have shown successful utilisation of whole bacterial cells in the ICA protocol enabling isolation of hmAbs targeting multiple disparate epitopes, thereby increasing the power of approaches such as reverse vaccinology 2.0 (RV 2.0) for bacterial vaccine antigen discovery.